2010
DOI: 10.1093/rfs/hhq077
|View full text |Cite
|
Sign up to set email alerts
|

Do Regulations Based on Credit Ratings Affect a Firm's Cost of Capital?

Abstract: The views expressed herein are those of the author(s) and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(60 citation statements)
references
References 25 publications
1
56
2
1
Order By: Relevance
“…Kisgen and Strahan (2009) investigated another form of entry when the SEC assigned NRSRO status to a fourth credit rating agency in the mid 1990s. The authors showed that the SEC's certification of the Dominion Bond Rating Service led to a statistically significant reduction in the cost of debt capital for the firms already rated by Dominion prior to its certification.…”
Section: Competition and The Quality Of Ratingsmentioning
confidence: 99%
“…Kisgen and Strahan (2009) investigated another form of entry when the SEC assigned NRSRO status to a fourth credit rating agency in the mid 1990s. The authors showed that the SEC's certification of the Dominion Bond Rating Service led to a statistically significant reduction in the cost of debt capital for the firms already rated by Dominion prior to its certification.…”
Section: Competition and The Quality Of Ratingsmentioning
confidence: 99%
“…2 Incorporating the regulatory use of ratings into the analysis is appealing because there is extensive empirical evidence that regulatory implications of ratings are a first-order concern for marginal investors; that is, ratings affect market prices through the channel of regulation, independent of the information they provide about the riskiness of securities (Kisgen and Strahan, 2010;Ashcraft, Goldsmith-Pinkham, Hull, and Vickery, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Kisgen and Strahan (2009) show that ratings-based regulations affect a firm's cost of debt capital. If costs play an important role in CDS responses to rating actions, then the decrease in market reaction we observe would imply that rating actions are less costly to firms in the post-crisis era.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…At the investment-grade boundary, regulations based on credit ratings are most binding and ratings changes from investment-grade to high-yield are the most costly (Kisgen (2006) and Kisgen and Strahan (2009)). We include BD and CBD as no prior study has examined this issue in a cross-sectional analysis of CDS performance 25 .…”
Section: A1 Regression Specificationmentioning
confidence: 99%